Identification of a highly potent and selective CB2 agonist, RQ-00202730, for the treatment of irritable bowel syndrome. Issue 2 (15th January 2015) - Iwata, Yasuhiro; Ando, Kazuo; Taniguchi, Kana; Koba, Naomi; Sugiura, Akemi; Sudo, Masaki
Graphical abstract: Abstract: Herein we report the identification of a highly potent and selective CB2 agonist, RQ-00202730 (40 ), obtained by lead optimization of the benzimidazole scaffold. Compound40 showed strong agonistic activity with an EC50 of 19 nM and excellent selectivity (>1300-fold) over the CB1 receptor. Compound40 displayed a dose dependent analgesic effect on TNBS-induced visceral hypersensitivity in rats by oral administration (ED50 0.66 mg/kg at 2.5 h after oral administration). In addition, 40 did not show a significant effect on body temperature in rats after oral administration at 300 mg/kg. These findings suggest that highly selective CB2 agonists will be effective agents for IBS therapy.